Inoculum dose–disease response relationships for the pea root rot pathogen, Aphanomyces euteiches, are dependent on soil type and other pathogens - Chatterton, Syama; Schwinghamer, Timothy D.; Pagé, Antoine; Davidson, Robyne Bowness; Harding, Michael W.; Banniza, Sabine (Frontiers in Plant Science, 2023)
The oomycete pathogen Aphanomyces euteiches was implicated for the first time in pea and lentil root rot in Saskatchewan and Alberta in 2012 and 2013. Subsequent surveys from 2014 – 2017 revealed that Aphanomyces root rot (ARR) was widespread across the Canadian prairies. The absence of effective chemical, biological, and cultural controls and lack of genetic resistance, leaves only one management option: avoidance. The objectives of this study were to relate oospore levels in autoclaved and non-autoclaved soils to ARR severity across soil types from the vast prairie landscape and to determine the relationship of measured DNA quantity of A. euteiches using droplet digital PCR or quantitative PCR to the initial oospore inoculum dose in soils. These objectives support a future end goal of creating a rapid assessment method capable of categorizing root rot risk in field soil samples to aid producers with pulse crop field selection decisions. The ARR severity to oospore dose relationship was statistically significantly affected by the soil type and location from which soils were collected, and did not show a linear relationship. For most soil types, ARR did not develop at oospore levels below 100 per g soil, but severity rose above this level, confirming a threshold level of 100 oospores/ g soil for disease development. For most soil types, ARR severity was significantly higher in non-autoclaved compared to autoclaved treatments, demonstrating the role that other pathogens play in increasing disease severity. There was a significant linear relationship between DNA concentrations measured in soil and oospore inoculum concentration, although the strength of the relationship was better for some soil types, and in some soil types DNA measurement results underestimated the amount of oospores. This research is important for developing a root rot risk assessment system for the Canadian prairies based on soil inoculum quantification, following field validation of soil quantification and relationship to root rot disease severity.